Sharing travel stories and behavioral outcomes: A case of travel. (October 2017) - Lee, Seonjeong Ally; Oh, Haemoon
Abstract: The benefits of tourism have been drawing a great deal of attention from tourists, community, and society alike. This study investigates how tourists' story sharing activities influence their post-purchase behavioral process, depending on different communication conditions. Two 2x2 between-subject experiments were conducted with recent travelers in the U.S. Results reveal tourists' post-purchase behavioral processes depend on what, how, and with whom they engage in post-trip story sharing activity. Findings contribute to the literature on purchase-driven happiness, self-enhancement, well-being, and communications by providing evidence on how different communication conditions alter the effects of tourists' story sharing on their post-purchase behavioral outcomes. Findings also suggest that destination marketers should apply strategies to encourage tourists' story sharing activity. Highlights: Tourists represent better post-purchase happiness, self-enhancement, well-being, and return intention when they share experiential purchase. Tie strength influences the relationship between tourists' sharing activity and their behavioral outcomes. Communication mode influences the relationship between tourists' sharing activity and their behavioral outcomes.